Effects of land use change on population survival of three wild rice species in China since 2001 - Chen, Hao; Dong, Shanshan; He, Zhizhou; Chen, Yuhong; Tian, Defeng; Liu, Yan; Wang, Yuguo; Zhang, Wenju; Li, Linfeng; Yang, Ji; Song, Zhiping (Frontiers in Plant Science, 2022)
Land use change stemming from human activities, particularly cropland expansion, heavily threatens the survival of crop wild relatives that usually occur nearby or scatter in farming systems. Understanding the impacts of land use change on wild populations is critical in forming the conservation decision-making of wild relatives. Based on the investigations on the population survival of three wild rice species (Oryza rufipogon, O. officinalis, and O. granulata) in China over the past 40 years (1978–2019), the effect of land use change during the past 20 years (2001–2019) on the natural populations of the three species was examined using the land use type data of satellite-based Earth observations (data from GlobCover). From 1978 to 2019, the number of populations (distribution sites) of the three wild rice species had decreased by 65%–87%, mainly because of the habitat destruction or disappearance caused by human-induced land use change. The three wild rice species display different habitat preferences, resulting in specific land use types surrounding their populations. In the recent 20 years, although the surrounding community composition of the wild rice population has been relatively stable, the surrounding vegetation cover area of the survived populations was significantly more extensive than that of the extinct ones (P < 0.05). These findings suggest that habitat vegetation plays a “biological barrier” role in the survival of wild populations through resisting or mitigating the disturbing impact of land use change on wild populations. This study provides not only direct guidelines for the conservation of wild rice but also new insights into the mechanisms underlying the influence of land use change on wild populations.